ON SOME ASPECTS OF THE INVERSION PROBLEM OF MAGNETOSTATICS - Chalupka S.; Vargova E. (My University, 2001)
Debye potentials and vector spherical harmonics were applied to a magnetostatic problem. By these mathematical methods it is shown that the inverse problem of the magnetostatics cannot be solved though the divergence of vector M is given.
Keywords: DIRECT PROBLEM; INVERSE PROBLEM; MAGNETOSTATICS